Benefits for emotional regulation of contact with nature: a systematic review - Ríos-Rodríguez, María Luisa; Rosales, Christian; Hernández, Bernardo; Lorenzo, Maryurena (Frontiers in Psychology, 2024)
Introduction: Exposure to natural environments, such as parks, forests, and green areas, is often linked to a decrease in stress, anxiety and depression, while contributing to improved emotional wellbeing. However, the relationship between exposure to nature and emotions, and in particular, with emotional regulation, is an evolving aspect of research with no clear conclusions. In this context, the environmental self-regulation hypothesis, suggests that people consciously or unconsciously use their physical environment to regulate their emotions. Method: To analyze the evidence of the relationship between contact with nature and emotional regulation, we conducted this review. Using the PRISMA statement as a reference, we conducted keyword searches in five databases in the period between 2013 and 2023. The databases selected were Scopus, Web of Science (WoS), PubMed, PsycINFO and ScienceDirect. Results: In addition, a manual search was carried out of journals in the research field. Initially, from which gray literature, reviews and duplicates were removed in a first step. The resulting articles were then filtered using their titles and abstracts. Subsequently, the abstracts of the 25 selected articles were reviewed and discussed by researchers to reach a final decision based on consensus about the adequacy of each paper. Finally, nine articles were included in the systematic review. Discussion: In general terms, this review suggests that research on the relationship between contact with nature and emotional regulation provides valuable insights into how natural environments can contribute to the emotional wellbeing and physical and mental health of the population.
Keywords: Naturaleza - Aspectos psicológicos; Connectedness to nature; Nature contact; Emotional regulation; Systematic review; Emotional self-regulation; Emotional management